Effects of cooling condition on microstructure and mechanical properties in laser rapid forming of 34CrNiMo6 thin-wall component. Issue 5 (February 2016) - Chunping, Huang; Xin, Lin; Fencheng, Liu; Jun, Cao; Fenggang, Liu; Weidong, Huang
Abstract Three kinds of cooling conditions, i.e., water cooling, metal cooling, and air cooling, were used to prepare 34CrNiMo6 steel thin-wall component by laser rapid forming (LRF) technology. The microstructure and mechanical properties of LRFed thin-wall component were investigated. Results indicate that 34CrNiMo6 steel thin-wall components without internal defect could be fabricated under three kinds of cooling conditions. Cooling condition has a significant effect on the microstructure and mechanical properties of LRFed thin-wall component due to the different tempering effects of subsequent LRFed process. The microstructure along the deposited direction is substantially uniform under the water-cooling condition, which consists of bainite and retained austenite. However, the microstructure of gradient structure changes from bainite to ferrite in thin walls produced under the metal-cooling and air-cooling conditions. The LRFed component under the metal-cooling condition has the best tensile property, of which the maximum tensile strength, yield ratio, and elongation reached to 993 MPa, 0.78, and 10.4 %, respectively. The LRFed component under the water-cooling condition is most brittle, and it is only 4 %. In contrast, the LRFed component under the air-cooling condition has the best plasticity.